2017
DOI: 10.17221/22/2017-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Differences in oviposition and egg quality of various genotypes of laying hens

Abstract: Tůmová E., Vlčková J., Chodová D. (2017): Differences in oviposition and egg quality of various genotypes of laying hens. Czech J. Anim. Sci., 62, 377-383.The differences in egg production traits in six laying hen genotypes (brown-egg hens Bovans Brown, Bovans Sperwer, ISA Sussex; white-egg hen Dekalb White; laying hens with tinted shells Moravia Barred and Moravia BSL) and the interactions of genotype and oviposition on egg quality were evaluated. The genotype affected the laying rate (P ≤ 0.003), mean sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Our results also indicated differences in egg weight between studied genotypes where Bovans Brown hens produced the heaviest eggs while ISA Brown hens had the lightest eggs. Similar findings were observed by Singh et al [ 3 ] and Tůmová et al [ 33 ] who reported a difference in egg weight according to different hen genotypes. The data of our study showed that ISA Brown and Moravia BSL laid eggs of lower egg weight (62.7 g and 63.5 g, respectively) compared to breed standard statements (63.1 g and 64.5 g, respectively), while Bovans Brown laid heavier eggs (64.3 g) when compared to breed standard statements (63.3 g) [ 29 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results also indicated differences in egg weight between studied genotypes where Bovans Brown hens produced the heaviest eggs while ISA Brown hens had the lightest eggs. Similar findings were observed by Singh et al [ 3 ] and Tůmová et al [ 33 ] who reported a difference in egg weight according to different hen genotypes. The data of our study showed that ISA Brown and Moravia BSL laid eggs of lower egg weight (62.7 g and 63.5 g, respectively) compared to breed standard statements (63.1 g and 64.5 g, respectively), while Bovans Brown laid heavier eggs (64.3 g) when compared to breed standard statements (63.3 g) [ 29 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, Bovans Brown genotypes showed the best eggshell quality parameters in comparison with ISA Brown and Moravia BSL genotypes. Similarly, better eggshell quality values of eggs produced by Bovans Brown genotype compared to other brown studied genotypes [ 33 ]. Franco-Jimenez and Beck [ 40 ] reasoned the better eggshell quality of brown eggs to the greater bone frame and stronger bone structure of brown egg layers that allow them to store a greater amount of Ca, leading to better eggshell formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the contrary to the results of this study, Samiullah et al (2016) found out that the heaviest eggs are laid early in the day and Tůmová & Ledvinka (2009) stated that the heaviest eggs were laid between 14:00 at 5:59. The significant effect of oviposition time on SI and ESS was determined, which is in accordance with the study from Tůmová et al (2017). Furthermore, YI and AI were also significantly affected by oviposition time, where higher values were observed at morning eggs (laid between 6:00 and 9:59).…”
Section: External and Internal Egg Quality Regarding The Breed And Ov...supporting
confidence: 89%
“…), age of animals, nutrition (Tang et al, 2015) housing system (Zita et al, 2018), storage conditions (Vlčková et al, 2019) and microbial contamination (Krunt et al, 2021). However, there are other factors that affect egg quality and one of them is oviposition (Hrnčár et al, 2013;Tůmová et al, 2017;Shaker et al, 2019). According to Tůmová et al (2017) time of the oviposition is an important factor and influences especially egg weight and eggshell quality parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation